2019
DOI: 10.1029/2019jd030900
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Stratospheric Sudden Warmings in the Beijing Climate Center Forecast System with Statistical Error Corrections

Abstract: Previous studies have reported that the predictive limit of stratospheric sudden warming (SSW) events in the Beijing Climate Center forecast system (BCC_CSM) is shorter than 2 weeks. This study continues to analyze the general characteristics of this model in forecasting SSWs and carries out a trial of error corrections. The ratio of the ensemble members that forecast the zonal wind reversal with a 5-day delay allowed (hit ratio) is higher for SSW events with a small decrease in the zonal mean zonal winds (mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
4
23
1
Order By: Relevance
“…For example, the SSW hit ratio for the 6 December initialization ensemble is higher (~50%) in those models than that in other models (<10%, below the 15–20% threshold in Rao, Ren, Chen, Liu, Yu, Hu, and Zhou ()). However, most models show a high hit ratio (>50%, exceeding the 15–20% threshold in Rao, Ren, Chen, Liu, Yu, Hu, and Zhou ()) for the 13 December initialization ensemble, which is common to nearly all models. Therefore, it is suggested that the average predictive limit for this SSW onset is at least 18 days.…”
Section: Prediction Of the 2019 New Year Ssw Eventmentioning
confidence: 82%
See 3 more Smart Citations
“…For example, the SSW hit ratio for the 6 December initialization ensemble is higher (~50%) in those models than that in other models (<10%, below the 15–20% threshold in Rao, Ren, Chen, Liu, Yu, Hu, and Zhou ()). However, most models show a high hit ratio (>50%, exceeding the 15–20% threshold in Rao, Ren, Chen, Liu, Yu, Hu, and Zhou ()) for the 13 December initialization ensemble, which is common to nearly all models. Therefore, it is suggested that the average predictive limit for this SSW onset is at least 18 days.…”
Section: Prediction Of the 2019 New Year Ssw Eventmentioning
confidence: 82%
“…The possible reasons for the longer predictability of this SSW event include the polar vortex displacement SSW type (for the initial SSW), the easterly QBO phase, and the MJO. The predictability of SSW events depends on the dominant wave number before the SSW onset (longer for wave‐1 type vortex displacement events than wave‐2 type vortex split events; see Taguchi, , ), and the boundary conditions (Butler & Polvani, ; Rao, Ren, Chen, Liu, Yu, Hu, & Zhou, ; Taguchi & Hartmann, ), and is longer by a few days when the MJO is strong (Garfinkel & Schwartz, ). While the initial wave‐1 disturbance is successfully forecasted at 18‐day leads, the splitting and persistence after onset are much more difficult to forecast in four different prediction MMEs initialized on 6, 13, 20, and 27 December. The predictability of this SSW onset depends on the model, but most models can forecast it at a lead time of 18 days, and some (e.g., NCEP, UKMO, and ECMWF) forecast it at 25‐day leads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During major SSWs, the polar vortex moves southward from the North Pole or splits into two daughter vortices, which are always classified as “displacement‐type SSW” events and “split‐type SSW” events. The displacement‐type SSWs are generally believed to be caused by strong planetary waves with a zonal wavenumber of 1 (wave 1), whereas the split‐type SSWs are mainly due to the enhancement of planetary waves with a zonal wavenumber of 2 (wave 2; e.g., Charlton and Polvani, 2007; Karpechko et al, 2018; Rao J et al, 2018, 2019a, 2019b). The statistical characteristics of the planetary waves during major SSWs and the two vortex types have also been verified by modeling analyses (e.g., Cao C et al, 2019; Liu SM et al, 2019).…”
Section: Introductionmentioning
confidence: 99%